Prevalence and Impact of Musculoskeletal Pain among Female Beauty Service Workers in Ujjain City: A Cross-Sectional Survey - Aanchal Bijlwan; Ruchi Mishra; Sanket Bajpai; Sanjiv K Jha; Devanshi Gupta; Kaushiki Muley (RGUHS Journal of Physiotherapy)
Introduction Musculoskeletal disorders MSDs are prevalent among female beauty service workers due to repetitive movements awkward postures and prolonged standing. These risk factors contribute to pain in various body regions particularly the lower back neck and shoulders. Despite the global acknowledgment of this issue limited data are available on musculoskeletal pain among female beauty service workers in India particularly in smaller cities like Ujjain.Methods This cross-sectional study was conducted among 50 female beauty service workers in Ujjain city. A structured questionnaire was used to assess demographic details the prevalence of musculoskeletal pain and associated risk factors. The primary outcome was the prevalence of musculoskeletal pain in specific body regions. Data analysis was done using descriptive statistics while chi-square tests examined relationships between independent variables and musculoskeletal pain.Results The study found that 70 of participants experienced lower back pain 60 reported neck pain and 50 had shoulder pain. Prolonged standing 80 repetitive movements 70 and poor ergonomics 60 were significant contributors to musculoskeletal pain. A correlation between years of experience and pain was identified with workers having over three years of experience being more likely to report pain 64.Conclusion The high prevalence of musculoskeletal pain among female beauty service workers in Ujjain underscores the need for ergonomic interventions and awareness programs to reduce the burden of MSDs in this population. Prolonged standing repetitive movements and poor ergonomic practices are significant risk factors that require attention.